2021
DOI: 10.5021/ad.2021.33.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Trauma, Physical Stress, and Occupation in Acral Melanoma: Analysis of 313 Acral Melanoma Patients in Korea

Abstract: Background Traumatic events are thought to be a cause of acral melanoma. However, little is known about the role of mechanical trauma or physical stress in the development of acral melanoma. Objective In our study, we evaluated the frequency of trauma, physical stress, and occupation in patients with acral melanoma and aimed to identify any pathological correlates of these factors. Methods We conducted a retrospective study of 313 acral melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A study of the Surveillance, Epidemiology, and End Results (SEER) registry from 1986 to 2005 found that ALMs accounted for 36%, 18%, and 9% of melanomas diagnosed in Blacks, Asian/Pacific Islanders, and Hispanic Whites, respectively, compared with 1% of melanomas in non-Hispanic Whites [ 71 ]. Due to its similar incidence across racial/ethnic groups and tendency to develop in the relatively sun-protected palms and soles, ALM is not thought to be associated with UV radiation [ 16 , 71 , 74 , 79 ] and instead has been linked to mechanical stress and injury [ 81 , 82 ].…”
Section: Photocarcinogenesismentioning
confidence: 99%
“…A study of the Surveillance, Epidemiology, and End Results (SEER) registry from 1986 to 2005 found that ALMs accounted for 36%, 18%, and 9% of melanomas diagnosed in Blacks, Asian/Pacific Islanders, and Hispanic Whites, respectively, compared with 1% of melanomas in non-Hispanic Whites [ 71 ]. Due to its similar incidence across racial/ethnic groups and tendency to develop in the relatively sun-protected palms and soles, ALM is not thought to be associated with UV radiation [ 16 , 71 , 74 , 79 ] and instead has been linked to mechanical stress and injury [ 81 , 82 ].…”
Section: Photocarcinogenesismentioning
confidence: 99%
“…Analysis in 313 Korean acral melanoma patients revealed that 26.8% reported traumatic events, and 29.1% experienced physical stress. The most common occupations were farmers and fishermen [ 49 ]. Physical stress, pressure, friction, maceration, irritation, and trauma may play roles in the pathogenesis of acral melanoma, and further studies are required to precisely determine the underlying molecular mechanism.…”
Section: Acral Melanomamentioning
confidence: 99%
“…Deletions in PTEN and CDKN2A are seen in up to 25% of cases [ 51 ]. The earliest genetic alteration in acral melanoma is the amplification of CCND1 , which is detected in the very early stages of acral melanoma in situ [ 11 , 49 ]. In Taiwan, NRAS / KRAS mutations, cell cycle aberrations, increased copy numbers in antiapoptotic genes BIRC2 , BIRC3 , and BIRC5 , and the amplification of receptor tyrosine kinase genes were significantly enriched in acral melanoma [ 54 ].…”
Section: Acral Melanomamentioning
confidence: 99%
“…Some studies have even suggested that trauma has a much greater impact on NAM than AM since NAM occurs more often in the thumb or big toe (75–90%), which are more susceptible to trauma [ 11 ]. One study has also found that NAM is more closely associated with trauma than non-nail acral melanoma (NNAM) ( p = 0.002) and that nails are most often affected by trauma, followed by toenails [ 7 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Non-nail acral melanomas are more common on the foot (82–88.6%) [ 4 , 5 , 15 ] and nail melanoma appears to be more common on the nails than on the toenails (58–61%) [ 7 , 12 , 15 , 20 ]. The prognosis for AM is worse than for CM.…”
Section: Clinical Characteristicsmentioning
confidence: 99%